2010
DOI: 10.4081/1747
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ageing on peroxidase activity and localization in radish (Raphanus sativus L.) seeds

Abstract: SUMMARYPeroxidase activity was assayed in crude extracts of integument, cotyledons and embryo axis of radish seeds, deteriorated under accelerated ageing conditions. Over five days of ageing, in which germination decreased from 100 to 52%, the enzyme activity in integument was higher than that in other seed parts, increasing in the first days of ageing and then decreasing sharply in extremely aged seeds. Polyacrylamide gel electrophoresis analysis showed four peroxidase isoenzymes with MM of 98, 52.5, 32.8 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 16 publications
(14 reference statements)
3
22
0
1
Order By: Relevance
“…This enables them, furthermore, to visualize a broader scope of the protein structure. Though it has been reported that each polypeptide chain is 31,965.5 Da, with a hemin plus Ca 21 of 656.578 Da, and a carbohydrate moiety of 1,418.4 Da, students have also found others M r values for POD [2,17,43]. According to this, students may discuss facts related to protein stability, recovery and maintenance of the tertiary structure after protein renaturalization by SDS removal in order to regain biological/catalytical activity.…”
Section: Determination Of Molecular Massmentioning
confidence: 99%
See 2 more Smart Citations
“…This enables them, furthermore, to visualize a broader scope of the protein structure. Though it has been reported that each polypeptide chain is 31,965.5 Da, with a hemin plus Ca 21 of 656.578 Da, and a carbohydrate moiety of 1,418.4 Da, students have also found others M r values for POD [2,17,43]. According to this, students may discuss facts related to protein stability, recovery and maintenance of the tertiary structure after protein renaturalization by SDS removal in order to regain biological/catalytical activity.…”
Section: Determination Of Molecular Massmentioning
confidence: 99%
“…PODs are ubiquitous in plants and have various physiological roles in plant tissues, including oxidation of a wide range of biomolecules by accumulation of active forms of oxygen, such as the superoxide radical (O 2 Á 2 ), the hydroxyl radical ( Á OH), and hydrogen peroxide (H 2 O 2 ) [2]. In plants, POD plays different roles, including construction, rigidification, and eventual lignifications of cell walls.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The studied isozymes are those of peroxidase (Px), polyphenol oxidase (PPO) and malate dehydrogenase (Mdh). Separation of isoenzymes of Px, PPO and Mdh were performed by Native PAGE ( Isozyms staining and detection (Scialabba et al, 2002) After electrophoresis, the gels were stained according to their enzyme systems with the appropriate substrate and chemical solutions then incubated at room temperature in dark for complete staining. In most cases, incubation for about 1 to 2 hr was enough.…”
Section: Isozymes Electrophoresismentioning
confidence: 99%
“…Accelerated ageing has been widely used to study the pattern of seed deterioration in various crops instead of waiting to obtain naturally aged seeds (Jatoi et al, 2001;Scialabba et al, 2002). Hence, with this backdrop, the present investigation was formulated to study the effect of nano size botanical powders for improving the performance of the aged soybean seeds.…”
Section: Introductionmentioning
confidence: 99%